2022
DOI: 10.1371/journal.pone.0267578
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of stress, burnout, and job satisfaction among mental healthcare professionals in Jeddah, Saudi Arabia

Abstract: Objective To assess the levels of stress, burnout, and job satisfaction among mental healthcare professionals in Jeddah City, Saudi Arabia. Methods A cross-sectional study was conducted on mental healthcare professionals in Jeddah between January 2017 and October 2018. Sociodemographic characteristics and levels of stress, burnout, and job satisfaction were assessed using the Perceived Stress Scale-14 (PSS-14), Maslach Burnout Inventory (MBI), and Job Satisfaction Scale (JSS). Descriptive statistics were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Married individuals often experience lower levels of burnout, 23 , 25 while those with higher income levels tend to exhibit greater job satisfaction. 30 , 35 , 36 This link suggests that financial stability and social support systems might play protective roles against burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Married individuals often experience lower levels of burnout, 23 , 25 while those with higher income levels tend to exhibit greater job satisfaction. 30 , 35 , 36 This link suggests that financial stability and social support systems might play protective roles against burnout.…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, the prevalence of stress among healthcare workers was 42% (Yubonpunt et al, 2022). This value is lower compare to 56% prevalence in Saudi Arabia (Alqarni et al, 2022). Previous studies in Ethiopia revealed that 37.8% to 68.2% of healthcare professionals had occupational stress (Salilih & Abajobir, 2014;Birhanu et al, 2018).…”
Section: Introductionmentioning
confidence: 75%
“…This may be due to the numerous challenges mental health nurses face, such as caring for individuals with mental disorders who are at risk of suicide, violence, and other dangers, working in restrictive and isolated settings, dealing with fear and guilt, and maintaining communication with patients and their caregivers while expending tremendous emotional effort [ 3 , 8 ]. Furthermore, mental health nurses often face increased stress due to acute patients and heavy workloads in mental health facilities [ 56 ]. Burnout has been linked to both medical and mental health issues, including but not limited to insomnia, migraines, impaired concentration, chronic tiredness, and irritability.…”
Section: Discussionmentioning
confidence: 99%